THE DEVELOPMENT OF TEACHING LEARNING MATERIALS MATHEMATICS WITH SCIENTIFIC APPROACH BASED ON PROBLEM BASED LEARNING TO LEARN CIRCLE FOR JUNIOR HIGH SCHOOL STUDENTS GRADE VIII - Rydlo Ega Putra; Marsigit . (Universitas Negeri Yogyakarta, 2017)
The aims of this research was to produce teaching learning materials such as lesson plan and worksheet with scientific approach based on problem based learning method to learn circle for junior high school studentsgrade VIII. The quality of teaching learning materials that was developed observation in terms of three aspect of quality these were validity, practicality, and effectiveness. The method used was the Research and Development (RD) with ADDIE model that includes analysis, design, development, implementation, and evaluation. This research was produced teaching learning materials such as lesson plan and worksheet. The validity score of the lesson plan was 4,10 with valid classification. While the validity score of worksheet was 4,06 with very valid classification. The result of the questionnaire from teacher and student showed that the teaching learning materialswas practical with total score 4,08. The result of observervation during the learning process showed good classification with percentage up to 89%. The result of student competency showed that teaching learning materials was very effective with percentage 85,71%.